Contribution to the analysis of the impact of process automation on the relevance of management control: Qualitative approach - BAL , Mohamed; AMELLAHOUCH , Fouzia (Revue Internationale du Chercheur, 2025)
Abstract This research examines the impact of the automation of management control on the relevance of managerial practices through a qualitative approach conducted in the Souss Massa region of Morocco. Based on semi-structured interviews with professionals, the study explores perceptions related to the introduction of artificial intelligence and digital tools in decision-making processes. The results show that automation helps improve the quality and speed of information processing, while raising challenges related to organizational adaptation, training, and the redefinition of the roles of management controllers. The study highlights the importance of reconciling technological innovation and human support to enhance the relevance and effectiveness of management control in a context of digital transformation.